Comparative Analysis of heighted structures using Analysis tool Staad, SAP2000 & ETABS considering Lateral Loads - Avaneesh Malviya; Dherendra Tiwari; Rakeh Patel (International Journal of Scientific Research in Civil Engineering, 2022)
Structural analysis comprises the set of physical laws and mathematics required to study and predicts the behaviour of structures. Structural analysis can be viewed more abstractly as a method to drive the engineering design process or prove the soundness of a design without a dependence on directly testing it. To perform an accurate analysis a structural engineer must determine such information as structural loads, geometry, support conditions, and materials properties. The results of such an analysis typically include support reactions, stresses and displacements. This information is then compared to criteria that indicate the conditions of failure. Advanced structural analysis may examine dynamic response, stability and non-linear behavior. In this paper we are presenting comparative analysis of four differently heighted 3 dimensional building frame considering seismic zone II using three different analysis tools i.e. staad.pro, SAP2000 and ETABS.In this paper we concluded that SAP2000 is suitable and providing linear results upto G+10 structure but as we raise the height above G+10 it is observed that ETABS is providing more precise result. Thus it is identified that Etabs is more linear for analysis of tall structures in comparison whereas staad.pro shows values higher for same loading condition in comparison.
Keywords: Staad.pro; SAP2000; ETABS; Structural Analysis; Forces; Moment; Displacement